2021
DOI: 10.4049/jimmunol.2001110
|View full text |Cite
|
Sign up to set email alerts
|

African Swine Fever Virus MGF-505-7R Negatively Regulates cGAS–STING-Mediated Signaling Pathway

et al.

Abstract: African swine fever virus (ASFV) is a devastating infectious disease in pigs, severely threatening the global pig industry. To efficiently infect animals, ASFV must evade or inhibit fundamental elements of the innate immune system, namely the type I IFN response. In this study, we identified that ASFV MGF-505-7R protein exerts a negative regulatory effect on STING-dependent antiviral responses. MGF-505-7R interacted with STING and inhibited the cGAS–STING signaling pathway at STING level. MGF-505-7R overexpres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
125
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(127 citation statements)
references
References 38 publications
2
125
0
Order By: Relevance
“…The pMGF505-7R/pA528R from MGF505 inhibits both IRF3 and ISRE promoter activation [ 43 ]. During the manuscript was being reviewed, ASFV CN/GS/2018 strain pMGF505-7R was found to promote ULK1-mediated STING degradation to negatively regulate IFN production [ 22 ]. In this study, we also found that nearly all members of pMGFs can inhibit IFN-β production, and pMGF505-7R shows the strongest inhibitory effect ( Fig 3B ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pMGF505-7R/pA528R from MGF505 inhibits both IRF3 and ISRE promoter activation [ 43 ]. During the manuscript was being reviewed, ASFV CN/GS/2018 strain pMGF505-7R was found to promote ULK1-mediated STING degradation to negatively regulate IFN production [ 22 ]. In this study, we also found that nearly all members of pMGFs can inhibit IFN-β production, and pMGF505-7R shows the strongest inhibitory effect ( Fig 3B ).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, attenuated ASFV strains which lack genes from MGF360 and MGF505 are more susceptible to type I IFNs [ 21 ]. Recently, a study shows that ASFV-encoded pMGF505-7R negatively regulates cGAS-STING Pathway by promoting ULK1-mediated STING degradation [ 22 ]. These results suggest that inhibition of the production of type I IFNs is an important strategy utilized by ASFV to evade host immune response and maintain infection.…”
Section: Introductionmentioning
confidence: 99%
“…IL-15 (but not IL-18) has been shown to confer NKG2Dmediated cytolytic function upon memory CD8 + T cells (Tough et al, 1999;Bastidas et al, 2014). NKG2D in CD8 + T cells can mediate costimulatory activity in the presence of TCR engagement (Groh et al, 2001: Jamieson et al, 2002Roberts et al, 2001;Maasho et al, 2005). However, NKG2D signaling can also occur in the absence of TCR engagement (Lanier et al, 2015).…”
Section: The Induction Of Natural Killer Receptors and Function In T Cells By Cytokinesmentioning
confidence: 99%
“…ASFV is a cytoplasmic dsDNA virus and mainly activates DNA-sensing cGAS-STING signaling pathway (16). Recently, two studies reported that ASFV pDP96R and pA528R (MGF505-7R) suppress cGAS-STING pathway mediated production of IFNs and proinflammatory cytokines by targeting TBK1/IKK and STING, respectively (17,18). However, the question whether the cGAS-STING pathway is suppressed by other ASFV viral proteins still persist.…”
Section: The Asfv Ps273r Protein Significantly Inhibits Cgas-sting Signaling Activitymentioning
confidence: 99%